2004
DOI: 10.1183/09031936.04.00058504
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol cyclosporin therapy in lung transplant recipients with bronchiolitis obliterans

Abstract: The majority of patients who develop bronchiolitis obliterans, after lung transplantation, die within 2-3 yrs after onset since treatment with conventional immunosuppression is typically ineffective. A case/control study was conducted in lung transplant recipients with biopsy-documented bronchiolitis obliterans to determine whether aerosol cyclosporin use contributed to increased survival.The cases comprised 39 transplant recipients who received open-label aerosol cyclosporin treatment in addition to conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 36 publications
2
32
0
1
Order By: Relevance
“…Data in lung transplantation have shown that inhaled CsA improved survival by reducing chronic graft rejection (considered equivalent to BO in allo-SCT recipients) with very high local immunosuppression and little additional systemic toxicity. 23,24 Challenges to the progress of medical management of BO include nonavailability of effective therapy. Our data showed early encouraging results using ECP in advanced refractory BO.…”
Section: Discussionmentioning
confidence: 99%
“…Data in lung transplantation have shown that inhaled CsA improved survival by reducing chronic graft rejection (considered equivalent to BO in allo-SCT recipients) with very high local immunosuppression and little additional systemic toxicity. 23,24 Challenges to the progress of medical management of BO include nonavailability of effective therapy. Our data showed early encouraging results using ECP in advanced refractory BO.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Local pulmonary delivery of CsA as nebulized liquid aerosols in lung transplant patients has been reported. 10,11 The improved response in a lung transplant patient by inhaled nebulized tacrolimus, another important immunosuppressant drug, for successful lung immunosuppression while significantly reducing systemic side effects and improving patient outcomes has been recently reported by the authors' group. 12 A metered-dose inhaler of CsA has been aerosolized in asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive proinflammatory signaling is a major component of airway pathology in cystic fibrosis (CF) as well as many other respiratory diseases (16,17). The delivery of CsA by aerosol in lung transplantation is currently being studied, not only to avoid systemic toxicities of the drug, but to decrease local immunoproliferative responses and bronchiolitis obliterans, a major complication of lung transplantation (18). Because cyclosporin acts through inhibition of the Ca 2Ï© -dependent phosphatase calcineurin, which is expressed in the airway epithelium, it seemed likely that cyclosporin could affect epithelial signaling in response to bacterial ligands.…”
mentioning
confidence: 99%